2014
DOI: 10.1371/journal.pone.0113600
|View full text |Cite
|
Sign up to set email alerts
|

A Single Chain Variant of Factor VIII Fc Fusion Protein Retains Normal In Vivo Efficacy but Exhibits Altered In Vitro Activity

Abstract: Recombinant factor VIII Fc (rFVIIIFc) is a fusion protein consisting of a single B-domain-deleted (BDD) FVIII linked recombinantly to the Fc domain of human IgG1 to extend half-life. To determine if rFVIIIFc could be further improved by maintaining the heavy and light chains within a contiguous single chain (SC), we evaluated the activity and function of SC rFVIIIFc, an isoform that is not processed at residue R1648. SC rFVIIIFc showed equivalent activity in a chromogenic assay compared to rFVIIIFc, but approx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…This observation implies that the deleterious intracellular processing by furin is mediated by a nonproteolytic chaperone role, as has previously been ascribed to furin (49). Isolated SC species of the long-acting FVIII-BDD-Fc fusion protein actually demonstrate 2-stage and in vivo clotting activity comparable with that of the heterodimeric species (50). We speculate that the residual B-domain released after thrombin activation may have a biochemical role in coagulation, as has been observed in FV (51).…”
Section: Discussionsupporting
confidence: 68%
“…This observation implies that the deleterious intracellular processing by furin is mediated by a nonproteolytic chaperone role, as has previously been ascribed to furin (49). Isolated SC species of the long-acting FVIII-BDD-Fc fusion protein actually demonstrate 2-stage and in vivo clotting activity comparable with that of the heterodimeric species (50). We speculate that the residual B-domain released after thrombin activation may have a biochemical role in coagulation, as has been observed in FV (51).…”
Section: Discussionsupporting
confidence: 68%
“…These studies also observed that the protein is fully activated by thrombin. Recently, novel single‐chain forms of FVIII that have increased affinity for VWF have been developed as a strategy for increasing the half‐life of the molecule; however, this results in only a modest half‐life extension . It is important to consider that each of these single‐chain forms is generated in a unique way (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Recurrent bleeding was not detected in FXI or carboxypeptidase B 2 gene‐deleted animals. Consequently, the incidence of rebleeding, survival or delayed blood loss of hemophilic mice following tail vein transection has been used to assess the efficacy of coagulation factor replacement products in murine preclinical studies .…”
Section: Resultsmentioning
confidence: 99%